PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI DINAS PERHUBUNGAN PROVINSI KALIMANTAN BARAT - B2041132025, Qaharuddin Nurli (Equator Journal of Management and Entrepreneurship (EJME), 2019)
To achieve organizational goals must be supported by human resources. Human resources are one of the most important assets in an organization, both governmental organizations, and private organizations. The success of the organization in achieving its goals is strongly influenced by the performance of its employees so that the organization is required to always develop and improve theÂ  performance of its employees. Based on previous research and associated with supporting theories that were raised by experts, this research was conducted to determine the influence of leadership and organizational culture on job satisfaction and its impact on the performance of employees of Dinas Perhubungan Provinsi Kalimantan Barat. The method used in this study is causality to determine the causal relationship between variables through observation and data collection through a questionnaire to explain the variables studied. This study uses Likert Scale to estimate the questionnaires. Data collection was carried out on all employees of Dinas Perhubungan Provinsi Kalimantan Barat with 72 people using the census method. This study uses path analysis to test the models and hypotheses formulated using Statistical Product and Service Solutions (SPSS) version 21. The results of this study reveal that leadership has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, leadership has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, and jobÂ  satisfaction has a positive and significant effect on employee performance.